1989
DOI: 10.1136/emj.6.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Pulse oximetry in the accident and emergency department.

Abstract: SUMMARYThe early detection and treatment of hypoxia is important to reduce patient morbidity in the accident and emergency department. At present, the commonly used methods all have practical difficulties in the urgent situations that prevail in the department. Pulse oximetry has recently become a method of choice in many anaesthetic and intensive care units for the continuous monitoring of oxygenation and the early detection of hypoxia.As similar conditions prevail in the accident and emergency departnent, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Pulse oximetry has been recommended during the insertion of invasive lines in pre‐medicated cardiac surgical patients and for postoperative patients as one study demonstrated that hypoxaemia can occur during the transfer from theatre to the recovery unit 14,15 . Studies evaluating the use of pulse oximetry in the emergency department found that it significantly changed medical treatment and has been recommended for all acutely ill patients presenting at the emergency department 16–18 . One study found that the introduction of pulse oximetry in the emergency department resulted in a 37% reduction in the number of arterial blood gas analyses and a 56% reduction in the number of cases involving three or more arterial blood gas analyses, without any increase in the number of adverse events 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Pulse oximetry has been recommended during the insertion of invasive lines in pre‐medicated cardiac surgical patients and for postoperative patients as one study demonstrated that hypoxaemia can occur during the transfer from theatre to the recovery unit 14,15 . Studies evaluating the use of pulse oximetry in the emergency department found that it significantly changed medical treatment and has been recommended for all acutely ill patients presenting at the emergency department 16–18 . One study found that the introduction of pulse oximetry in the emergency department resulted in a 37% reduction in the number of arterial blood gas analyses and a 56% reduction in the number of cases involving three or more arterial blood gas analyses, without any increase in the number of adverse events 19 .…”
Section: Resultsmentioning
confidence: 99%